Recent Advances in Knowledge Management - Mohiuddin, Muhammad; Samim Al Azad, Md; Ahmed, Shammi (IntechOpen, 2022)
Recent Advances in Knowledge Management investigates the multidimensional aspects of knowledge management by exploring different perspectives and practices as well as existing theories of effective knowledge management in a changing world. Chapters address such topics as tacit knowledge, knowledge management frameworks, informally structured domains of knowledge management, and more. Beyond understanding the nature of knowledge management processes in different kinds of organizations, this book examines the nature of knowledge management focusing on what we know and how we know it.